2023
DOI: 10.1007/s12144-022-04121-8
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and mental health in healthy adults, a topic of primary prevention and health care, empirical results from two online studies

Abstract: Oral health is an important, yet often neglected aspect of health and well-being. Among geriatric populations, oral diseases, poor oral health, and reduced oral hygiene behavior are major comorbid factors of geriatric diseases such as dementia, cardiovascular diseases, or mental health conditions. However, little is known so far about the relationships between oral health and mental health in the younger adult population, who is yet not suffering from any disorder. In the present manuscript the results of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Our study showed that age had no significant association with oral health. However, several studies have shown or proved otherwise that lower mental status and lower self-rated health were associated with being at risk for oral health [ 24 ]. This may be due to the deteriorating mental condition associated with older age.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that age had no significant association with oral health. However, several studies have shown or proved otherwise that lower mental status and lower self-rated health were associated with being at risk for oral health [ 24 ]. This may be due to the deteriorating mental condition associated with older age.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization's report from 2022, oral diseases affect about 3.5 billion individuals, which accounts for about half of the world's population [2]. Oral disorders can dramatically reduce the quality of life [3] and increase the risk of developing or worsening other disorders, including somatic [4] and mental disorders [5]. Burning mouth syndrome (BMS) is a chronic, debilitating condition characterized by a persistent burning sensation [6].…”
Section: Introductionmentioning
confidence: 99%